Posttraumatic growth among head and neck cancer survivors with psychological distress. Issue 1 (25th February 2016) - Holtmaat, K.; van der Spek, N.; Cuijpers, P.; Leemans, C. R.; Verdonck‐de Leeuw, I. M.
Abstract: Background: Information on posttraumatic growth (PTG) among head and neck cancer (HNC) survivors with a high level of distress is limited. The aim of this cross‐sectional study was to investigate the occurrence of PTG among distressed HNC survivors and its association with anxiety, depressive, nicotine, and alcohol use disorders and health‐related quality of life. Methods: Seventy‐four HNC survivors with psychological distress (Hospital Anxiety and Depression Scale (HADS) anxiety > 7 and/or HADS depression > 7) completed the Posttraumatic Growth Inventory, which comprises five subscales: relating to others, new possibilities, personal strength, spiritual change, and appreciation of life, and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire. Anxiety, depressive, nicotine, and alcohol use disorders were measured using the Composite International Diagnostic Interview. Results: Moderate to high Posttraumatic Growth Inventory (PTGI) scores occurred in 10% of the HNC survivors with distress. The mean total PTGI score was 30.8 (SD = 19.7), with the highest mean score on the subscale relating to others. A multivariate regression model consisting of tumor stage, anxiety disorder, alcohol use disorder, and social functioning predicted total PTGI score best ( F (4, 64) = 7.565, p  < .000, R 2  = .321). Conclusions: The presence of PTG in this population of distressed HNC survivors was low. PTG occurred most in the domain of relating to others. Among distressed HNC survivors, higher PTG was associated with lower tumor stage, absence of an anxiety disorder, absence of an alcohol use disorder, and better social functioning. Copyright © 2016 John Wiley & Sons, Ltd.